Comparative efficacy of topical commercial Chinese polyherbal preparation for vulvovaginal candidiasis: a network meta-analysis - Wu, Lizheng; Jing, Shangwen; Li, Na; Cao, Dandan; Pei, Fangli; Luo, Yantong; Chen, Xiaoxin; Huang, Yingjie; Zeng, Cheng (Frontiers in Pharmacology, 2025)
ObjectiveTo systematically evaluate the differences in the efficacy of commonly used topical commercial Chinese polyherbal preparations (CCPPs) for vulvovaginal candidiasis (VVC), and to provide evidence-based reference for clinical drug regimens.MethodsComputer searched major Chinese and English literature databases, and collected randomized controlled trials (RCTs) of external use of CCPPs combined with conventional treatment (CT, test group) versus CT alone (control group) in patients with VVC. After screening the literature, the quality of the included studies was assessed using the risk of bias assessment tool recommended in 5.3 of the Cochrane Handbook. Outcome data for each outcome measure were extracted and a network meta-analysis was performed using Stata 15.0.ResultsA total of 74 RCTs with a total of 8,151 patients were included, nine interventions were involved. The results of network meta-analysis showed that, Fufang Shajiziyou suppository combined with CT was more effective in improving the negative conversion rate and controlling the recurrence rate of Candida albicans. Kangfu gel combined with CT had the better effect in relieving pruritus. Baofukang suppository combined with CT was the most effective in reducing leukorrhea. Fufukang spray combined with CT had fewer adverse reactions.ConclusionThe addition of CCPPs to CT may acquire a better curative effect in patients with VVC and external does not significantly increase the occurrence of adverse reactions. However, due to the low quality of the included literature, larger-scale, higher-quality clinical studies are still needed.Systematic Review RegistrationPROSPERO, NO: CRD42023410244.